Fabrication of Solid‐State Flexible Fiber Supercapacitor Using Agave Americana Derived Activated Carbon and Its Performance Analysis at Different Conditions. Issue 21 (21st December 2016) - Pandi, Karuppiah; Sankar, Kalimuthu Vijaya; Kalpana, Dharmalingam; Lee, Yun Sung; Selvan, Ramakrishnan Kalai
Abstract: Flexible fiber symmetric supercapacitors were fabricated using activated carbon derived from Agave americana having uniform pores because of chemical activation using two different activating agents, KOH (K‐AC) and NaOH (Na‐AC). The X‐ray diffraction analysis revealed the formation of amorphous carbon. The Fourier transform infrared and X‐ray photoelectron spectroscopies infers the presence of oxygen functional groups. The N2 adsorption/desorption study revealed a bimodal type pore size distribution in both the samples. A maximum specific surface area of 1122.7 m 2 g −1 is obtained for K‐AC. The fabricated symmetric supercapacitor (K‐AC∥PVA+H2 SO4 ∥K‐AC) exhibits a maximum length specific capacitance of 18 mF cm −1 with good capacitance retention and cycle life. Subsequently, the effects of temperature, device length, and flexibility of the device were studied by fabricating different shapes (normal, zigzag, and spiral). Finally, the device was tested in a practical application in a flexible mode, which was integrated with an energy harvesting system, indicating good reliability of the device. Abstract : Flexible fiber symmetric supercapacitors were fabricated using activated carbon derived from Agave Americana . The fabricated symmetric supercapacitor (K‐AC∥PVA+H2 SO4 ∥K‐AC) exhibited a maximum length capacitance of 18 mF cm −1 with good capacitance retention and cycle life. Subsequently, the effects of temperature, device length, and flexibility of the device were studied by fabricating different shapes (normal, zigzag, and spiral).